1999
DOI: 10.1002/(sici)1099-1166(199911)14:11<915::aid-gps36>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Community care for patients with Alzheimer's disease and non‐demented elderly people: use and satisfaction with services and unmet needs in family caregivers

Abstract: Supporters of elderly people with AD were significantly more involved in providing care than supporters of non-demented people. Judgement on the health, social relations and financial status of their families was significantly worse in AD supporters than in supporters of non-demented elderly people. Although the former made more use of available health and social services than the control population, they did appear to make little use of such services, not only because of lack of information but also for logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mullan (1993) found that care receivers resisted use of community services, whereas Harrison and Neufeld (1997) described the reluctance of caregivers to use community services. Several investigators have also noted the concern that caregivers express over the cost of community services (Dello-Buono et al, 1999;Liken & King, 1995;Mullan, 1993). Similarly, others who have studied use of community services have reported the problem of quality of care (Mullan, 1993;Liken & King, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullan (1993) found that care receivers resisted use of community services, whereas Harrison and Neufeld (1997) described the reluctance of caregivers to use community services. Several investigators have also noted the concern that caregivers express over the cost of community services (Dello-Buono et al, 1999;Liken & King, 1995;Mullan, 1993). Similarly, others who have studied use of community services have reported the problem of quality of care (Mullan, 1993;Liken & King, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Families who care for relatives with dementia have reported lacking information about services and the ability to access services, preferring services with tailored interventions, needing financial and psychological support, wanting interventions within the home, and being unsatisfied with the quality of care (Dello-Buono, Busato, Mazzetto, Paccagnella, Aleotti, Zanetti, Bianchetti, Trabucchi, & De Leo, 1999). Liken and King (1995) reported in their study of AD family caregivers' (N ¼ 32) use of home health aide services that the costs outweighed the benefits, especially when hassles, loss of control, service fit, and knowledge deficits of aides were taken into consideration.…”
Section: Introductionmentioning
confidence: 99%